RADT-11. INCREASED USE OF HYPOFRACTIONATED RADIOTHERAPY IN ELDERLY PATIENTS WITH GLIOBLASTOMA IN THE UNITED STATES FROM 2004-2015. (12th November 2021) - Hall, Matthew; Kalman, Noah; Odia, Yazmin; Tom, Martin; Mohler, Alexander; Rubens, Muni; Walters, Rameen; Shah, Sunny; Mallory, Chase; Gates, Kevin; Von Werne, Katherine; Mehta, Minesh
Abstract: PURPOSE/OBJECTIVES: The prognosis for glioblastoma in elderly patients is poor; randomized trials have demonstrated comparable survival following adjuvant radiotherapy (RT) using conventional or hypofractionation. We used the National Cancer Database (NCDB) to measure trends in the use of hypofractionated RT in glioblastoma patients 70 years of age and older. MATERIALS AND METHODS: The NCDB was queried for elderly glioblastoma patients treated with a known RT dosing schema from 2004-2015 (n=10, 089 patients). Adjusted logistic regression was used to assess the association of treatment year with the annual percentage of patients who received hypofractionated RT (including 40-45 Gy/15 fractions, 34 Gy/10 fractions, or 25 Gy/5 fractions). Average annual percentage change (AAPC) was compared to determine if a significant change occurred in the use of hypofractionated RT during this period. Multivariable regression was used to determine factors associated with the use of hypofractionated RT. RESULTS: Use of hypofractionated RT was stable between 2.5-3.3% from 2004-2008 and then monotonically increased to 22.2% by 2015 (p< 0.001). The AAPC in the use of hypofractionated RT was +29.6% per year (p< 0.001), with a corresponding decline in conventional fractionation over this period. No significant change was observed in palliative dosing schema or the use of stereotactic radiosurgery. On logistic regression, age, treatment at an academic center, Charlson Deyo score ≥2, and treatment year were significantly associated with utilization of hypofractionated RT. In this dataset, 24.8% of patients who received either conventional or hypofractionated RT died within 3 months of beginning RT. CONCLUSIONS: During 2008-2015, an increasing number of elderly patients with glioblastoma received hypofractionated RT. Hypofractionated RT should be considered in elderly patients to shorten the time spent receiving medical care during the final months of life. Attention to hospice care is also important, especially in those with brief expected survival who may derive limited benefit from RT.